ROLE OF EMOTIONAL INTELLIGENCE IN CONFLICT MANAGEMENT STYLES AMONG NURSES - Liaqat, Mehwish; Jahangir, Nazia; Ghafoor, Iqra; Fatima, Dr. Qurratulain; Nisar, Saira (The journal of contemporary issues in business and government, 2021)
Emotional intelligence is anessential factor that may measure individual’s performance in their professional lives beyond their daily lives, increase or decrease their success, contribute to the measurement of managerial qualities, and improve organizational communication and interaction. The present study aimed to identify the role of emotional intelligence on conflict management styles among nurses. The sample consistedof 400 nurses, and the model was taken from four public and four private hospitals located in Multan city. A purposive sampling technique was used to collect the data, and the age range was between 25 to 45 years. Two research instruments were used to collect the data. The emotional intelligence scale developed by Schutte et al. (2018) was used and consisted of 33 items. The interpersonal conflict inventory developed by Rahim (1983) was used and consisted of 28 items. This study showed the relationship between emotional intelligence and conflict management styles; integration, obliging, dominating, and compromising are positively correlated with the score of emotional intelligence, and avoiding was negatively correlated withemotional intelligence. The results further showed a significant difference in age on emotional intelligence among nurses, and there is also a significant difference in age on conflict management styles among nurses. Moreover, the results revealed a significant difference on emotional intelligence and conflict management styles among the nurses of public and private hospitals.